THE ROLE OF TAWAKAL AS A SPIRITUAL REGULATION MECHANISM IN OVERCOMING FUTURE ANXIETY - Nanda Aulia Fadilah; Nuralam Syah; Radhwa Afifah Adzra (Universitas Islam Negeri Mataram, 2026)
This study specifically analyzes the role of tawakal as a spiritual regulatory mechanism in helping Islamic Religious Education students at UIN Sunan Gunung Djati cope with future anxiety, which is defined as an individual's inability to face future uncertainty. The purpose of this research is to understand the dynamics of future anxiety in Islamic Religious Education students and analyzing the role of tawakal as a spiritual regulatory mechanism in managing future anxiety based on students' subjective experiences. Using a qualitative phenomenological approach, data were collected through in-depth interviews and observations with three Islamic Religious Education students and two campus religious administrators. Data were later analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion. Research results show that anxiety arises in academic, career, financial, and personal maturity aspects. Triggered by internal factors such as low self-confidence and external factors such as family pressure and academic demands. Tawakal helps calm emotions, increase self-acceptance, and strengthen readiness to face uncertainty, especially regarding the future. The effectiveness of tawakal is supported by spiritual closeness, namely a condition in which an individual has a strong relationship with God and social and religious support. At the same time, obstacles stem from a mistaken understanding of tawakal and the determination of negative thoughts. This study confirms that tawakal is a spiritual strategy that can reduce anxiety about the future.